2012
DOI: 10.1007/s12018-012-9126-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin and the Regulation of Glucose Metabolism

Abstract: Uncarboxylated osteocalcin enhances insulin and adiponectin release and improves glucose tolerance in mice. Data in humans do not unequivocally support a role for osteocalcin in glucose homeostasis. Changes in the amount of uncarboxylated osteocalcin induced by vitamin K or warfarin treatment are not associated with changes in glucose and insulin concentrations. Interventional studies in humans, designed to detect small changes in insulin secretion and action attributable to changes in uncarboxylated osteocalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…[22] Vitamin K2-7 plays a role in carboxylating osteocalcin, a Vitamin K-dependent protein, which has been shown to regulate the glucose homeostasis. [23] A decade-long study of 38,094 Dutch population aged 20-70 found that the participants who consumed the most dietary Vitamin K were 20% less likely to develop type 2 diabetes than the participants with the lowest intake of Vitamin K. [22] Vitamin K2 is linked to lowered risk of developing type 2 diabetes. The risk of developing type 2 diabetes drops for every 10 mcg increase in Vitamin K2 intake.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Vitamin K2-7 plays a role in carboxylating osteocalcin, a Vitamin K-dependent protein, which has been shown to regulate the glucose homeostasis. [23] A decade-long study of 38,094 Dutch population aged 20-70 found that the participants who consumed the most dietary Vitamin K were 20% less likely to develop type 2 diabetes than the participants with the lowest intake of Vitamin K. [22] Vitamin K2 is linked to lowered risk of developing type 2 diabetes. The risk of developing type 2 diabetes drops for every 10 mcg increase in Vitamin K2 intake.…”
Section: Discussionmentioning
confidence: 99%
“…In NAFLD children, there is a positive correlation between ucOCN and ADPN [ 94 ]. In mice, ucOCN enhances ADPN release and improves glucose tolerance [ 95 ].…”
Section: Molecular Mechanism Of Osteocalcin In Flhs Chickensmentioning
confidence: 99%
“…Dr. Karsenty claimed that we cannot conclude that osteocalcin is not a hormone without the osteocalcin injection experiments. Treatment with vitamin K, which reduces uncarboxylated osteocalcin, does not affect glucose metabolism in humans, and warfarin, which increases uncarboxylated osteocalcin, has no effect on glucose metabolism in rats and there are no reported studies in humans [7,8]. Absence of osteocalcin has no effects on glucose metabolism, testosterone synthesis, and muscle mass in mice [2,3].…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%